Comparison of Open versus Laparoscopic Repair for the Treatment of Hollow Viscus Perforation - Singh, Jasvinder; Gill, Amritpal Singh (Asian Journal of Medical Research, 2020)
Background: Acute abdomen is severe abdominal pain. It occurs suddenly. The present study was conducted to compare open versus laparoscopic repair for the treatment of hollow viscus perforation. Subjects and Methods: The present study was conducted on 72 patients of both genders. All patients were divided into 2 groups. In group I patients, laparoscopic repair was performed and in group II patients, open repair was performed. Variables such as time taken for resumption of daily activities and operative time were recorded in all patients. Results: Abdominal distension occurred before pain in 10 in group I and 9 in group II patients, after pain in 6 in group I and 5 in group II and with pain in 20 in group I and 22 in group II patients. Vomitus was bilious seen 17 in group I and 16 in group II and no vomiting 19 in group I and 20 in group II patients. Fever was seen in 22 in group I and 17 in group II, history of drug intake was seen 17 in group I and 19 in group II, history of alcohol intake was seen in 13 in group I and18 in group II patients, smoking in 20 in group I and 14 in group II and tobacco usage 15 in group I and 9 in group II patients. Diagnosis was gastric perforation seen in 7 in group I and 8 in group II, ileal perforation seen 3 in group I and 4 in group II and duodenal perforation seen 26 in group I and 24 in group II patients. The difference was significant (P< 0.05). Conclusion: Authors found that Laparoscopic repair group had lower surgical time and early resumption of daily activities as compared to open surgery group.